Optimization of drift controlled type 2 steel tier frames - Criswell, M. E., author; Duvall, Lawrence L., author; Civil Engineering Department, Colorado State University, publisher (Colorado State University. Libraries, 1977)
This study develops a method for optimizing the distribution of structural steel in mid- and highrise braced framing systems to satisfy stiffness requirements as necessary to limit excessive lateral drift. This optimization procedure incorporates a term designated as the "deflection influence parameter", defined as the member deflection contribution divided by the member volume. Members with the highest deflection influence parameters are the least efficient in providing structural stiffness, and are therefore modified by the optimization routine which systematically increases the appropriate member areas. The proposed method, although developed for determinate pinned trusses, gives very close to optimal solutions for indeterminate single-bay braced frames. A computer program capable of performing this optimization routine for structures with many members is also presented, together with specific design examples selected to demonstrate the simplicity and efficiency of the method.
CER77-78LLD-MEC-1.
August 1977.
Keywords: Structural frames; Steel, Structural